A qualitative study of Traditional Chinese Medicine nursing needs in elderly patients after surgery for mixed hemorrhoids (老年混合痔术后患者中医护理干预需求的质性研究) - ZHOU Hui (周惠); HUANG Xiaoqi (黄小齐); SU Juyan (苏菊艳); YANG Haiyan (杨海燕); ZHANG Ting (张婷) (Journal of International Translational Medicine Limited, 2023)
Objective To deeply understand the Traditional Chinese Medicine (TCM) nursing needs of elderly patients after surgery for mixed hemorrhoids, and provide reliable basis for medical staff to carry out targeted TCM nursing intervention. Methods The phenomenological method was used to conduct a semi-structured in-depth interview with 10 elderly patients undergoing surgery for mixed hemorrhoids. The final interview results were obtained by using the thematic analysis method. Results The current nursing situation of the elderly patients with mixed hemorrhoids after operation can be summarized into four themes, namely, medication by syndrome differentiation, nutrition by syndrome differentiation, treatment by syndrome differentiation and nursing by syndrome differentiation. Conclusion The medical staff should explore and apply a scientific, reasonable and practical TCM nursing intervention plan according to the particularity of the elderly patients with mixed hemorrhoids, therefor promote the postoperative rehabilitation. (目的 深入了解老年混合痔患者术后中医护理干预需求, 为医护人员有针对性开展中医护理干预提供可靠依据。方法 采用现象研究学方法对贺州市某三级甲等中医医院符合条件的10名老年混合痔患者进行半结构式深入访谈, 采用主题分析法逐步分析, 得出最终的访谈结果。结果 老年混合痔患者术后中医护理干预现状及需求可以归纳为四方面主题, 即辨证施药、辨证施食、辨证施术、辨证施养。结论 医护人员应该根据老年混合痔术后患者的特殊性探索一套科学、合理、实用性强的中医护理干预方案并应用, 促进康复。)